The Role of Digital Marketing and Product Innovation in Increasing the Competitiveness of Gabinfla MSMEs in the Digitalization Era - Amalia Salsabilla; Muhammad Hamdan Ali Masduqie (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of digital marketing and product innovation on increasing the competitiveness of Gabinfla Micro, Small, and Medium Enterprises (MSMEs) in the digitalization era. The method used is a quantitative approach. The population in this study were consumers of Gabinfla MSMEs, with a sample of 101 respondents obtained through accidental sampling techniques. Data collection was carried out using a questionnaire with a five-point Likert scale. The data analysis technique used was multiple linear regression with the help of Statistical Product and Service Solutions (SPSS) 26, through stages of validity and reliability testing, as well as classical assumption tests including normality, multicollinearity, and heteroscedasticity. The results of the study indicate that digital marketing and product innovation, both partially and simultaneously, have a significant effect on the competitiveness of Gabinfla MSMEs. The coefficient of determination (Adjusted R²) value of 0.894 indicates that 89.4% of the variation in competitiveness can be explained by the two independent variables, while the remainder is influenced by variables not used in the study. These findings confirm that the use of digital marketing and the development of creative and sustainable product innovations can increase the competitiveness of MSMEs amidst increasingly competitive markets in the digital era.